Pengaruh Green Fiance, Pertumbuhan Ekonomi dan Keterbukaan Perdagangan Terhadap Emisi CO2 Bukti dari Negara Anggota OKI - Herianto; Tenri Lala, Andi Ajeng Tenri Lala; Nurpasila (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
Sustainable development is currently not only measured by the economic growth of a country or region but goes further than that. One of them, through the stability and maintenance of the environment. This study aims to look at the relationship between green financing, economic growth, trade barriers and CO2 emissions specifically in countries that are members of the OIC cooperation. This study uses a quantitative approach with a panel data estimation model with the help of testing using the eviews 9 statistical application. Samples were used in 8 countries namely Bahrain, Bangladesh, Brunei Darussalam, Indonesia, Malaysia, Jordan, Kazakhstan, Sudan and Saudi Arabia, with sample fees using purposive example. Furthermore, data was obtained from the official website of the world bank and the Islamic Financial Service Board (IFSB). The peculiarity of this research is that it shows that environmentally friendly financing, economic growth and the rise of trading have a positive effect on CO2 emissions. The results of this study confirm that development policies in several OIC member countries have had a significant impact on pollution in these countries and the presence of Islamic banks through financing in the green economy sector has not shown an impact that can reduce CO2 emissions.